REVISED INVENTORY OF LEARNING PROCESSES. VALIDATION FOR SPANISH VERSION - Esteban, Manuel; Ruiz, Cecilia; Cerezo Ramírez, Fuensanta (Anales de Psicología / Annals of Psychology)
The objective of this research is to adapt and validate a questionnaire of Learning styles for the population of Murcia (Spain). Sample consists of 478 adolescents, preferably from 15 to 19 years old, in their Secondary Education in any of its different categories (F.P.; E.S.O. and B.U.P.), and first year of University. ILP-R questionnaire was translated and adapted to the Spanish educative context, which was elaborated by Schmeck and cols. In 1991, and subsequently validated. Our data point out that its reliability and validity (performed through factorial analysis), confirm this instrument as a valid and reliable test to detect and measure learning styles of adolescents in Murcia.